Electromyographic activities of muscles in the shoulder and elbow joints during elbow flexion-extensions with different velocities in the sagittal and horizontal planes - Angelova Silvija K.; Raikova Rositsa T.; Markova Nikol N. (Sciendo, 2024)
Study aim: Properly processed surface electromyographic signals (EMGs) provide a suitable means for the estimation of muscle activity, including their synergistic and antagonistic action. This study aimed to investigate changes in the activity of elbow and shoulder muscles due to changes in the velocities of elbow flexion/extension motions in the sagittal and horizontal plane without and with an additional load of 0.5 kg on the wrist using processed EMGs of six muscles and the angle of the elbow joint.